Family satisfaction and self-efficacy among low-income adolescents during the COVID-19 pandemic: A comparative analysis of parents' educational attainment - Lee, Jaewon; Allen, Jennifer; Lim, Hyejung; Choi, Gyuhyun; Jung, Jiyu (Frontiers in Psychiatry, 2022)
Purposes: Given that the period from middle to high school is important to develop and cultivate self-efficacy, reduced support in low-income families might negatively influence the development of self-efficacy among low-income students since COVID-19. This study aims to investigate the association between family satisfaction and self-efficacy among low-income students since COVID-19 and the moderating effect of parents’ educational attainment on the relationship. Methods: A total of 255 low-income students in South-Korea were selected for the final sample. The PROCESS macro 3.4 for Statistical Product and Service Solutions was used to analyze the data. Results: Family satisfaction was positively related to self-efficacy among low-income students. There was a significant moderating effect of parents’ educational attainment on the relationship between family satisfaction and self-efficacy among low-income students during the COVID-19 pandemic. Discussion: Financial support and COVID-19 benefits should be prioritized to low-income families with adolescents to improve family relationships, leading to increase self-efficacy among low-income students. Social welfare programs targeting family relationships in low-income households should be especially targeted toward low-income households without a parent who received higher education. Life-long education should be provided to parents in low-income families who did not gain higher education as their educational attainment influences the self-efficacy of their adolescent children.